ECONOMIC ANALYSIS OF ENVIRONMENTAL CARRYING CAPACITY BASE ON LAND SUPPLY AND DEMAND OF AGRICULTURE AND LIVESTOCK BY USING SYSTEM INTERRELATIONSHIP MODEL - NENDA, AGUS
Environmental carrying capacity in agriculture and livestock context is land ability to produce commodities to support human needs. Today, environmental carrying capacity analysis equation have no environmental loss calculation yet that occur by agriculture and livestock activities. The aims of study is to determine the environmental carrying capacity status of agricultural and livestock activities in Kecamatan Kertasari considering of environmental cost which consist of soil aspect and river water quality aspect base on land supply and demand. The study xamines the linkage components of agriculture, livestock and environment using system interrelationship model that analyzed economically. The results of analysis show the components that influence of the sustainable agriculture are household, horticultural, rice field, dairy farm, pasture, chemical fertilizers, pesticides, manure, soil particles, river, and dairy feces. Based on the calculations, the total amount of environmental costs is 72.6 billion rupiahs per year. It affect to the environmental carrying capacity on land. Calculation shows the carrying capacity is deficit of 7,842 hectares, where the land supply (SL) < land demand (DL). The land supply is currently 4,209 hectares whereas the land demand is 12,050 hectares. This is shows that the land only supports for 23,398 persons or 35% from total population.